EFEKTIVITAS DAN EFISIENSI PELATIHAN PERHITUNGAN VOLUME DAN ANGGARAN BIAYA PADA BANGUNAN INFRASTRUKTUR NAGARI DI KECAMATAN PAUAH DUO KABUPATEN SOLOK SELATAN - Nadra Mutiara Sari; Juniman Silalahi; Muvi Yandra (CIVED, 2019)
Abstract—. Pauh Duo Subdistrict, Solok Selatan Regency is one of the subdistricts that have village funds (BUMNag) that are scattered in every area which aims at equitable development. Therefore the community must know how to manage and implement these funds, especially in infrastructure buildings (buildings, roads, bridges, and drainage). Training to the community is one of the alternatives so that the funds can be absorbed effectively and efficiently. The training focused on calculating the volume and Budget Plan (RAB) of an infrastructure building. This is addressed to residents that involved in managing and implementing village funds in four villages in the Pauah Duo sub-district, namely Nagari Pauah Duo Nan Batigo, Nagari Kapau Alam Pauah Duo, Nagari Luhak Kapau Alam Pauah Duo, and Nagari Alam Pauah Duo. The training was held from the 26th- 29th of September 2019. The results of the training are included in an effective and efficient category. The final evaluation results are in the outstanding category. It can be concluded that the implementation of the training went smoothly with very satisfying results and could improve the quality of public knowledge.Keywords : BUMNag, Training volume and Budget Plan (RAB), Pauh Duo Subdistrict,